Significance of ontology for designing stakeholder-oriented applications/ Shah Jahan Miah, Michael McGrath and Ahmad Zam Hariro Samsudin - Miah, Shah Jahan; McGrath, Michael; Samsudin, Ahmad Zam Hariro (Fakulti of Information Management, Universiti Teknologi MARA, 2015)
Ontology provides formal explicit description of problem domains that contribute to structuring system solution. Over the past decades various applications have been developed using ontology technique for providing various user access benefits. This makes the ontology as one of the prominent techniques specially to systemize problem domains. In this paper, we describe importance of ontology development through our experience that has been gathered in two user-oriented applications development projects. The projects were designed to address issues related to user access and understandability on developed systems, in which we promote unique significance of ontology specially for developing system solution. Findings from our studies suggest that ontology enables provisions to reflect user's common understandbility for developing stakeholder oriented applications that trun to miximuse various user benefits.